Regulation of Staphylococcal Penicillinase Synthesis - Imsande, John (1972)
5-Methyl tryptophan was found to be an efficient inducer of penicillinase synthesis in Staphylococcus aureus. Addition of actinomycin D or tryptophan to the culture medium shuts off the 5-methyl tryptophan-induced synthesis of penicillinase with an apparent half-life of approximately 1 to 2 min, respectively. Hence, in the induction of penicillinase synthesis, 5-methyl tryptophan seems to function as a structural analogue of penicillin rather than by becoming incorporated in proteins and thereby creating faulty penicillinase repressor or antirepressor. This conclusion is supported by similarities in the structures of the two compounds as revealed by solid atomic models. The fact that S. aureus exposed to (14)C-penicillin in the absence of protein synthesis failed to synthesize penicillinase at an increased level when cell growth was resumed strongly suggests that a protein involved in the regulation of penicillinase synthesis must be synthesized in the presence of the penicillinase inducer. In turn, this observation suggests that the penicillinase inducer promotes penicillinase synthesis by directing the penicillinase regulatory protein (i.e., the penicillinase antirepressor) to acquire a different conformation when it is synthesized in the presence of the penicillinase inducer. A working model for the regulation of penicillinase synthesis based on these and other data has been constructed and is presented.